2014
DOI: 10.1007/s10557-014-6545-6
|View full text |Cite
|
Sign up to set email alerts
|

Sparstolonin B Attenuates Hypoxia-Induced Apoptosis, Necrosis and Inflammation in Cultured Rat Left Ventricular Tissue Slices

Abstract: Purpose Ischemia/reperfusion results in tissue damage, a rapid increase in cytokines and chemokines and inflammatory cell infiltration. Herein we investigated the ability of a selective TLR2/4 antagonist, Sparstolonin B (SsnB), to protect rat cultured left ventricular tissue (LV) slices from hypoxic injury by inhibiting the myocardial inflammatory response independent of inflammatory cell infiltration. Methods and Results Media Lactate dehydrogenase (LDH) levels were measured to reflect hypoxia-induced cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…It has been reported that long-term hypoxia can induce various harmful effects, including myocardium hypertrophy, 2 apoptosis, 3 and necrosis. 4 Thus, preventing cardiomyocyte apoptosis and necrosis is an important challenge in the treatment of MI.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that long-term hypoxia can induce various harmful effects, including myocardium hypertrophy, 2 apoptosis, 3 and necrosis. 4 Thus, preventing cardiomyocyte apoptosis and necrosis is an important challenge in the treatment of MI.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SsnB can induce reactive oxygen species generation and promote apoptotic cell death in neuroblastoma cells of different genetic backgrounds (Kumar et al, 2014). In addition, further research has indicated that SsnB is able to protect mice against endotoxin shock by inhibiting production of multiple cytokines and lung dysfunction (data belongs to our institute) and attenuate hypoxia-induced apoptosis, necrosis and inflammation in cultured rat left ventricular tissue slices (Liu et al, 2014a). All of these results suggest that SsnB could be a promising drug candidate for treating inflammatory cardiovascular disease and neuroblastoma therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Several chemical constituents such as trans-stilbenoids, triterpenoids, flavonoids and phenolic acids have been reported (Nakajima et al, 1987;Powell et al, 1987;Kang et al, 2008;Zhang and Wang, 2009;Cui et al, 2012). In addition, further research has indicated that SsnB is able to protect mice against endotoxin shock by inhibiting production of multiple cytokines and lung dysfunction (data belongs to our institute) and attenuate hypoxia-induced apoptosis, necrosis and inflammation in cultured rat left ventricular tissue slices (Liu et al, 2014a). Selectively, it can block TLR2-and TLR4-mediated macrophages inflammatory responses (Liang et al, 2011), attenuate hypoxia-reoxygenation-induced cardiomyocyte inflammation (Liu et al, 2014b), suppress lipopolysaccharide-induced inflammation in human umbilical vein endothelial cells (Liang et al, 2013, b) and inhibit pro-angiogenic functions and blocks cell cycle progression in endothelial cells (Bateman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among the components therein, astragalus and Salvia are the most commonly used compatibility drugs. In our previous studies, we focused on investigating the roles of TCM in CHD [9][10][11][12]. In particular, it is evident that astragalus membranaceus, the main component of astragalus membranaceus, and tanshinone IIA, the main component of Salvia miltiorrhiza, can effectively improve myocardial ischemic injury [13].…”
Section: Introductionmentioning
confidence: 99%